2013
DOI: 10.1016/j.tcs.2012.10.059
|View full text |Cite
|
Sign up to set email alerts
|

More effective crossover operators for the all-pairs shortest path problem

Abstract: The all-pairs shortest path problem is the first non-artificial problem for which it was shown that adding crossover can significantly speed up a mutation-only evolutionary algorithm. Recently, the analysis of this algorithm was refined and it was shown to have an expected optimization time (w. r. t. the number of fitness evaluations) of Θ(n 3.25 (log n) 0.25 ).In contrast to this simple algorithm, evolutionary algorithms used in practice usually employ refined recombination strategies in order to avoid the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Crossover operators subsequently have been shown to be useful in more cases. These include Ising models [16,49], the TwoPaths instance class of the problem of computing unique input-output sequences [30], some instance classes of the vertex cover problem [39], and the all-pairs shortest path problem [10,9,11]. Meanwhile, on the contrary, Richter et al [44] produced the Ignoble Trail functions where a crossover operator was shown to be harmful.…”
Section: Related Workmentioning
confidence: 99%
“…Crossover operators subsequently have been shown to be useful in more cases. These include Ising models [16,49], the TwoPaths instance class of the problem of computing unique input-output sequences [30], some instance classes of the vertex cover problem [39], and the all-pairs shortest path problem [10,9,11]. Meanwhile, on the contrary, Richter et al [44] produced the Ignoble Trail functions where a crossover operator was shown to be harmful.…”
Section: Related Workmentioning
confidence: 99%
“…However, these techniques cannot be directly applied to the analyses of more realistic GAs incorporating a crossover operator. Several results were indeed available proving that crossover is useful (Jansen and Wegener, 2005;Watson and Jansen, 2007;Oliveto et al, 2008;Doerr et al, 2010;Kötzing et al, 2011;Neumann et al, 2011;Sudholt, 2012;Doerr et al, 2013), but they rely heavily on elitist selection operators. Moreover, mostly only upper bounds on the running time of crossover-based algorithms were available.…”
Section: Introductionmentioning
confidence: 99%
“…the unary unbiased black-box complexity of OneMax was proven to be Θ(n log n) [6,16]. Together with the rather old question of whether crossover is useful in evolutionary algorithms (which was previously answered positively [8,15,19]), this inspired a number of works on higher-arity unbiased algorithms, since many crossovers are binary unbiased operators.…”
Section: Introductionmentioning
confidence: 99%